Simulação de cenários e formulação estratégica: O caso de um varejista multicanal - Zadinello, Viridian Afonso (2021)
The objective of this work was to elaborate a strategic planning by simulation of scenarios and action plans with strategies for each simulated scenario in a multichannel retailer that operates with the physical and virtual store. The model used to simulate the scenarios and formulate the strategies contained in the action plan was the Rojo Model (2006), which has five levels. The first step was to perform the application of level 1 of the Rojo Model, which is the Delphi technique, followed by applying strategic tools, simulation of scenarios, elaboration of strategies, and formalization of the action plan. The results achieved helped the organization reformulate its mission, vision, and values, as well as in the creation of strategies for several possible scenarios. These strategies will serve as a form of prevention if any simulated scenarios come to fruition.